Residual HCV-RNA and Elevated Platelet-to-Lymphocyte Ratio Predict Poor Long-Term Outcomes in Patients with Chronic Hepatitis C After Treatment - Anna Wróblewska; Mateusz Gliwiński; Magda Rybicka; Małgorzata Cheba; Beata Lorenc; Piotr Trzonkowski; Krzysztof P. Bielawski; Katarzyna Sikorska (Infectious Diseases and Therapy)
Abstract Introduction Despite achieving sustained viral response (SVR) after treatment with direct-acting antivirals (DAAs), the risk of liver disease progression and extrahepatic complications in chronic hepatitis C (CHC) remains. We aimed to determine the role of residual HCV-RNA in peripheral blood mononuclear cells (PBMCs), a condition known as occult hepatitis C (OCI), and systemic inflammatory markers as predictors of long-term outcomes in patients treated with DAAs. Methods We followed 42 patients treated with DAAs with OCI status determined after therapy, for a median of 6.3 years. Plasma levels of 16 cytokines and chemokines were measured in samples collected 12–15 months after end of treatment. Samples from 10 patients with CHC and 8 healthy controls were used for comparison. Results The presence of HCV-RNA in PBMCs correlated with adverse outcomes [odds ratio (OR) 17.6, confidence interval (CI) 1.8–175); p = 0.011], and an elevated platelet-to-lymphocyte ratio (PLR) was associated with mortality. Patients with residual HCV-RNA had higher levels of macrophage-derived chemokine (MDC/CCL22) (p = 0.026) and interleukin-18 (IL-18) (p = 0.009), but lower levels of fractalkine/CX3CL1 (p = 0.007), interferon gamma (IFNγ) (p = 0.016), IL-13 (p = 0.009), and lymphotoxin alpha (LTα) (p = 0.007) compared to those without OCI. The profile of immune mediators in patients with OCI differed more from healthy controls than from patients without OCI. Conclusions These findings suggest that residual HCV-RNA and elevated PLR are potential predictors of poor long-term outcomes in patients treated with DAAs, possibly linked to an altered cytokine/chemokine response.